Effective probiotics’ delivery system: problems and perspectives - Starovoitova, Svitlana; Spivak, Mykola (My University, 2023)
Microencapsulation of probiotics in polymer microcapsules successfully protects them from aggressive and variable conditions of the gastrointestinal tract, and also allows the delivery of live cells of probiotic microorganisms without loss of their functional activity to the target biotope of the host organism. Microcapsules also protect probiotic cells during storage in a wide range of temperatures and can significantly extend the shelf life of the final product. Co-microencapsulation of prebiotics with probiotic microorganisms can further increase the survival of the latter during storage and passage through the gastrointestinal tract. Мікрокапсулювання пробіотиків у полімерні мікрокапсули успішно захищає їх від агресивних та мінливих умов ШКТ, а також дозволяє доставляти живі клітини пробіотичних мікроорганізмів без втрати їх функціональної активності до цільового біотопу організму-хазяїна. Мікрокапсули також захищають пробіотичні клітини під час зберігання в широкому діапазоні температур і можуть значно подовжити термін придатності кінцевого продукту. Спільне мікрокапсулювання пребіотиків з пробіотичними мікроорганізмами може додатково підвищити виживання останніх під час зберігання та проходження через ШКТ.
Keywords: пробіотичні мікроорганізми; системи доставки; мікробіота; microbiota; кафедра біотехнології і мікробіології